Konservasi Preventif Koleksi Lukisan di Galeri Bumi Parawira Kota Bogor - Solihat, Zakia Aulia; Rachman, Margareta Aulia (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
Preventive conservation is an action taken to slow down deterioration and prevent damage to collections and cultural materials in information institutions. Preventive conservation in galleries is carried out to prevent damage to collections, especially paintings. Bumi Parawira Gallery has a collection of paintings while the possibility of damage to the painting collection at Bumi Parawira Gallery is inevitable. This research aims to analyze the preventive conservation of painting collections at Bumi Parawira Gallery. This research was conducted using qualitative methods and data collection was done through interviews, observations, and surveys. The results showed that the preventive conservation of painting collections at Bumi Parawira Gallery is carried out by looking at damage factors and potential losses that will occur such as vandalism, theft, pollutants, and dissociation.